Role and Interpretation of Antifungal Susceptibility Testing for the Management of Invasive Fungal Infections - Frederic Lamoth; Russell E. Lewis; Dimitrios P. Kontoyiannis (Journal of Fungi, 2020)
Invasive fungal infections (IFIs) are associated with high mortality rates and timely appropriate antifungal therapy is essential for good outcomes. Emerging antifungal resistance among Candida and Aspergillus spp., the major causes of IFI, is concerning and has led to the increasing incorporation of in vitro antifungal susceptibility testing (AST) to guide clinical decisions. However, the interpretation of AST results and their contribution to management of IFIs remains a matter of debate. Specifically, the utility of AST is limited by the delay in obtaining results and the lack of pharmacodynamic correlation between minimal inhibitory concentration (MIC) values and clinical outcome, particularly for molds. Clinical breakpoints for Candida spp. have been substantially revised over time and appear to be reliable for the detection of azole and echinocandin resistance and for outcome prediction, especially for non-neutropenic patients with candidemia. However, data are lacking for neutropenic patients with invasive candidiasis and some non-albicans Candida spp. (notably emerging Candida auris). For Aspergillus spp., AST is not routinely performed, but may be indicated according to the epidemiological context in the setting of emerging azole resistance among A. fumigatus. For non-Aspergillus molds (e.g., Mucorales, Fusarium or Scedosporium spp.), AST is not routinely recommended as interpretive criteria are lacking and many confounders, mainly host factors, seem to play a predominant role in responses to antifungal therapy. This review provides an overview of the pre-clinical and clinical pharmacodynamic data, which constitute the rationale for the use and interpretation of AST testing of yeasts and molds in clinical practice.